2017
DOI: 10.1108/ejm-10-2015-0712
|View full text |Cite
|
Sign up to set email alerts
|

Marketing agency – client relationships: towards a research agenda

Abstract: European Journal of Marketing1 Marketing agency-client relationships: towards a research agenda. Abstract Purpose -Since agencies play a pivotal role in operationalising marketing strategy, this relationship is central to marketing theory, management and practice. This article presents the first systematic review of the literature relating to the relationships between organisations and their marketing agencies, the agency-client relationship, and presents a concept matrix that identifies the key areas of inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 130 publications
0
29
0
Order By: Relevance
“…The context for the research is that of marketing agencies and their clients working in a co-dependent relationship. A recent literature review of the extant research on marketing agency -client relationships identified co-creation as a key theme for future research to develop stronger theoretical foundations in this area (Keegan, Rowley and Tonge, 2017).…”
Section: Agencies and Clients: A Co-creative Professional Relationshipmentioning
confidence: 99%
“…The context for the research is that of marketing agencies and their clients working in a co-dependent relationship. A recent literature review of the extant research on marketing agency -client relationships identified co-creation as a key theme for future research to develop stronger theoretical foundations in this area (Keegan, Rowley and Tonge, 2017).…”
Section: Agencies and Clients: A Co-creative Professional Relationshipmentioning
confidence: 99%
“…In summary, the literature on agencies and clients has recognised that the contribution of both agency and client is important in creating the end result, but this has not been addressed specifically as an example of co-creation of value. In an extensive review of the agency/client literature, Keegan, Rowley and Tonge (2017) identify an agenda for future research which includes co-creation, as a promising new direction. Keegan, Rowley and Tonge (2017) specifically mention the work on S-D Logic, as significant to this agenda.…”
Section: Hence Rq1: What Service Is Provided Between Marketing Agencimentioning
confidence: 99%
“…In an extensive review of the agency/client literature, Keegan, Rowley and Tonge (2017) identify an agenda for future research which includes co-creation, as a promising new direction. Keegan, Rowley and Tonge (2017) specifically mention the work on S-D Logic, as significant to this agenda. This article responds to this call in the light of the knowledge gap discussed above.…”
Section: Hence Rq1: What Service Is Provided Between Marketing Agencimentioning
confidence: 99%
“…Keller (2016) identified the challenges that clients face due to the everincreasing choice of brand touch points and proposed that client/agency relationships needed to be explored further. Keegan, Rowley, and Tonge (2017) recently produced a comprehensive literature review of client/agency relationships with an emphasis on marketing-in-practice and identified a number of future research themes. First, they call for research that generates good practice knowledge and solutions to challenging issues.…”
Section: Introductionmentioning
confidence: 99%
“…They also identify the need to reflect changing marketing communications where clients work with numerous agencies across digital, mobile, and social media platforms and to recognise the increasing role of trust in enabling the co-creation of marketing messages. This paper addresses these issues raised by Keegan et al (2017) and moves our understanding forward by examining client/agency relationships through the IMC lens.…”
Section: Introductionmentioning
confidence: 99%